Formation of Binuclear Metal Complexes with Multidentate Schiff-base Oxime Ligand: Synthesis and Spectral Investigation - Issa, I. O.; Al-Jeboori, M. J.; Al-Dulaimi, J. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The new polydentate Schiff-base oxime (1E,1`E)-2hydroxy-3-((E)-(2-((E)-2hydrxy3-((E)-(hydroxyimino)methyl)-5-methylbenzyldeneamino)ethylimino)methyl)-5methylbenzaldehyde oxime H4L and its binuclear metal complexes with Mn(II), Fe(II), Co(II) and Cu(II) are reported. The reaction of 2,6 diformyl–4–methyl phenol with hydroxyl amine hydrochloride in mole ratios of 1:1 gave the precursor (E)-2-hydroxy-3((hydroxyimino)methyl)-5-methylbenzaldehyde. Condensation reaction of precursor with ethylenediamine in mole ratios of 2:1 gave the new N4O2 Schiff-base oxime ligand H4L. Upon complex formation, the ligand behaves as a tribasic hexadantate species. The mode of bonding and overall geometry of the complexes were determined through physico-chemical and spectroscopic methods. These studies revealed tetrahedral geometries for Mn(II), Fe(II), Co(II) complexes and square planar geometry about Cu(II) complex of general formulae [M2(HL)](Cl)(H2O). Molecular structure of the for Mn(II), Fe(II), Co(II) complexes has been optimised by CS Chem 3D Ultra Molecular Modeling and Analysis Program and supported four coordinate geometry.